Brachial-Ankle Pulse Wave Velocity is Associated with the Risk of New Carotid Plaque Formation: Data from a Chinese Community-based Cohort - Yang, Yao; Fan, Fangfang; Kou, Minghao; Yang, Ying; Cheng, Guanliang; Jia, Jia; Gao, Lan; Zhou, Zechen; Chen, Dafang; Zhang, Yan; Huo, Yong (Scientific reports, 2018)
Artery stiffness is an independent marker for atherosclerotic cardiovascular diseases. However, whether the brachial-ankle pulse wave velocity (ba-PWV) is related to new carotid plaque formation is unresolved. This study aimed to investigate the association between baseline ba-PWV and new carotid plaque formation in a Chinese community-based population without carotid plaques at baseline. This study population consisted of a total of 738 participants from an atherosclerosis cohort in Beijing, China. After a mean 2.3-year follow-up, the incidence of carotid plaques were 21.2% and 36.5% in the groups with ba-PWV < 1,400 cm/s and ≥1,400 cm/s, respectively. Compared with baseline ba-PWV < 1,400 cm/s group, ba-PWV ≥ 1,400 cm/s group was significantly associated with the incidence of new carotid plaque formation (odds ratio [OR] = 2.14, 95% CI: 1.50–3.03, P < 0.01), even after adjusting for common risk factors (OR = 1.52, 95% CI: 1.02–2.25, P = 0.04). Furthermore, there was a strong relationship between baseline ba-PWV and carotid plaque formation in subjects with ba-PWV < 1,400 cm/s, but no such relationship was found in subjects with baseline ba-PWV ≥ 1,400 cm/s. In conclusion, this study suggests that baseline ba-PWV is independently associated with the risk of carotid plaque formation in a Chinese community-based population.